RANCANG BANGUN SISTEM INFORMASI PURCHASING BERBASIS WEB MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) PADA PT. KOMINDO BIZOLUSI - Raka Juliandra; Gerard Richardo Girsam; Muhammad Ryan Hidayat; Sharyanto Sharyanto; Alexius Ulan Bani (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
The purchasing information system at PT. Komindo Bizolusi still has limitations, as it only functions as a transaction input medium without supplier data analysis and process automation. Supplier selection is also conducted subjectively without a systematic approach. This study aims to design a web-based purchasing information system using the Analytical Hierarchy Process (AHP) method to support supplier selection decisions. The research methods include observation, interviews, and literature study, with system development using the Waterfall method and UML design. The system is built using Laravel and MySQL and tested using Black Box Testing. The results show that the system produces consistent weighting with a value of 0.0760 (<0.1) and provides objective supplier rankings.